Studi Deskriptif Kesulitan Belajar Matematika Materi KPK dan FPB Serta Penanganannya Pada Siswa Kelas IV - Nisa Ul 'Alimah 'Alimah; Endang Widi Winarni; Irfan Supriatna (JURIDIKDAS, 2022)
This research sought to identify and describe the difficulties in learning mathematics on the materials of KPK and FPB as well as efforts to handle them in class IV A students at SD Negeri 03 Bengkulu City. The research method used is descriptive qualitative with data collection techniques of observation, interviews, and document analysis of practice questions. The aspect studied was the process of learning mathematics from KPK and FPB material to identify difficulties and the teacher's efforts to handle them. Based on the results of the research, four learning difficulties were found (1) Difficulties in instilling concepts, in the form of low student concentration, as well as the teacher's efforts to handle them by attracting the attention and focus of students by counting together, and conducting question and answer questions to students. (2) Difficulty understanding the concept, in the form of difficulty understanding the concept of multiples of numbers, the concept of prime numbers, and the concept of powers of numbers, as well as the teacher's efforts to handle them by reviewing the previous subject matter at the next meeting. (3) Difficulties in numeracy skills, in the form of errors in performing arithmetic operations in answering questions, as well as the teacher's efforts to handle them by accompanying students to complete calculations on questions, and giving routine practice questions to develop numeracy skills. (4) Difficulties in applying the concept, in the form of errors in solving word problems, so that they do not solve problems in the questions, the teacher's efforts to handle them by giving remedial programs to students.